Chondroitin sulfate-polyethylenimine copolymer-coated superparamagnetic iron oxide nanoparticles as an efficient magneto-gene carrier for microRNA-encoding plasmid DNA delivery1. Issue 18 (14th May 2015) - Lo, Yu-Lun; Chou, Han-Lin; Liao, Zi-Xian; Huang, Shih-Jer; Ke, Jyun-Han; Liu, Yu-Sheng; Chiu, Chien-Chih; Wang, Li-Fang
<x xml:space="preserve">Abstract</x> MicroRNA-128 (miR-128) is an attractive therapeutic molecule with powerful glioblastoma regulation properties.